Internal Audit of the Supply Chain Management Benefits as the Main Tool of the Finance Mechanism - V. Bubnovskaya, Tatiana; E. Vasilenko, Marina (ExcelingTech, 2020)
Supply chain management are the main tool of the finance mechanism in the international companies. There are various application of supply chain management according to various classification criteria. The aim of internal audit is to make recommendations for improving the efficiency and effectiveness of operations and to help management in achieving the projected business goals. The subject of this paper is the analysis of various fields of internal audit of the supply chain as well as evaluating the characteristics of individual elements of the chain with consideration to appropriateness and integration of those elements. This article presents the author application of supply chain management in the finance part of the company for the development.